Estimating China's Capital Flows-at-risk: The Case of Potential US Financial Sanctions - Daehee Jeong (KDI Journal of Economic Policy, 2022)
The arena of strategic competition between the US and China is expandable from international politics, trade and commerce to finance. What would happen if financial sanctions against China are imposed by the US? Would US financial sanctions lead to a sudden outflow of foreign capital and a liquidity crisis in China? We try to address these questions by estimating China's capital flows-at-risk with the CDS premium on Chinese sovereign funds. We follow Gelos et al. (2019) in setting up a quantile regression model from which China's foreign capital flow-at-risks are estimated. Based on our analysis of China's monthly capital flow data, we find that a rise in the CDS premium has statistically significant negative impacts on China's foreign capital flows-at-risk, mainly in banking flows. However, the analysis also found that due to favorable global conditions, an increase in the CDS premium is unlikely to trigger a shift to a sudden outflow of foreign capital at the moment. Meanwhile, this study found no statistically significant correlation between Korea's capital flows-at-risk and the CDS premium, suggesting that the negative impact of US financial sanctions on China would not increase the probability of capital flight from Korea in a significant manner.
Keywords: C21; F32; F51; 330; Financial Sanctions; US-China Competition; Capital Flow-at-risk; Macro-prudential Policy; Quantile Regression